THE PREDICTIVE ROLE OF PRINCIPALS’ PERSONALITY IN ENHANCING SCHOOL PERFORMANCE: EVIDENCE FROM JUNIOR HIGH SCHOOLS IN SOUTH SULAWESI - Usman, Usman; burhan, imron; amran, muhammad (Universitas Labuhanbatu, 2025)
Purpose – The purpose of this research is to examine how various aspects of a principal’s personality, such as extraversion, agreeableness, emotional stability, and openness, contribute to the overall performance of junior high schools in South Sulawesi.Methodology – This study employed a quantitative research design, allowing the researcher to systematically test hypotheses and analyze the relationship between the principal’s personality and distributed leadership on school performance. To assess the impact of the two independent variables on school performance, this study utilized multiple regression analysis. Teacher responses gathered from public junior high schools in South Sulawesi served as the primary data source and were analyzed quantitatively to evaluate the predictive role of each variable in shaping school performance.Findings – The study's results showed that the principal's personality traits of agreeableness and openness significantly predicted school performance in junior high schools in South Sulawesi. Agreeableness received a regression coefficient of β = 0.21 (p < .05), while openness had a coefficient of β = 0.19 (p < .05), indicating that both traits have a meaningful influence on school outcomes. Teachers described principals with strong agreeableness as individuals who worked well with others, were sincere, and willingly offered support, which in turn encouraged harmonious relationships and teamwork among school staff. Overall, the results suggest that fostering agreeableness and openness in school leaders is crucial in enhancing school performance and promoting a healthy educational environment.Contribution – This research highlights that the personality characteristics of school principals, particularly openness and agreeableness, are crucial factors that enhance school performance by strengthening management quality and improving accountability